PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) MATA PELAJARAN IPA MATERI GAYA BERBANTUAN MEDIA PEMBELAJARAN DIGITAL FLIPBOOK TERHADAP KEMAMPUAN BERPIKIR REFLEKTIF SISWA KELAS IV SEKOLAH DASAR - Sholikah, Syafia putri; Rosmiati; Juniarso, Triman (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research is based on students' low reflective thinking skills in science learning, as well as the lack of use of interactive digital media. This research aims to determine the influence of the use of the problem based learning (PBL) model assisted by flipbook digital learning media on reflective thinking abilities. This research used the pre-test post-test method in experimental class 1 and experimental 2. The subjects of this research were class IV students consisting of two groups, namely experimental class 1 and 2. This data collection technique was from tests and questionnaires given to students. The results of the research showed that there was a significant increase in students' reflective thinking abilities who were taught using the problem based learning model assisted by digital flipbook learning media in style material. This is proven by higher pre-test and post-test scores. Based on these results, it can be concluded that the application of the problem based learning model assisted by flipbook digital learning media can improve the reflective thinking abilities of class IV students. Based on the data obtained, the average N-gain in experimental classes 1 and 2 experienced a significant increase of 0.70. It can be concluded that there is an influence on the use of the problem based learning (PBL) model assisted by digital flipbook learning media in science subjects style material assisted by digital flipbook learning media on the thinking abilities of fourth grade elementary school students.